Protective effect of COVID-19 vaccination against long COVID syndrome: A systematic review and meta-analysis. Issue 11 (10th March 2023) - Watanabe, Atsuyuki; Iwagami, Masao; Yasuhara, Jun; Takagi, Hisato; Kuno, Toshiki
Highlights: The effects of COVID-19 vaccination on long COVID remains inconclusive. Vaccination before SARS-CoV-2 infection was associated with a lower risk of long COVID. Vaccination after SARS-CoV-2 infection was not associated with symptomatic changes of long COVID. Vaccination before SARS-CoV-2 infection can be recommended to reduce long COVID. Abstract: Background: The relationship between coronavirus disease 2019 (COVID-19) vaccination and long COVID has not been firmly established. We conducted a systematic review and meta -analysis to evaluate the association between COVID-19 vaccination and long COVID. Methods: PubMed and EMBASE databases were searched on September 2022 without language restrictions ( CRD42022360399) to identify prospective trials and observational studies comparing patients with and without vaccination before severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) infection. We also included studies reporting symptomatic changes of ongoing long COVID following vaccination among those with a history of SARS-CoV-2 infection. Odds ratios (ORs) for each outcome were synthesized using a random-effects model. Symptomatic changes after vaccination were synthesized by a one-group meta -analysis. Results: Six observational studies involving 536, 291 unvaccinated and 84, 603 vaccinated (before SARS-CoV-2 infection) patients (mean age, 41.2–66.6; female, 9.0–67.3%) and six observational studies involving 8, 199 long COVID patients (mean age, 40.0 to 53.5; female, 22.2–85.9%) who received vaccination after SARS-CoV-2 infection were included. Two-dose vaccination was associated with a lower risk of long COVID compared to no vaccination (OR, 0.64; 95% confidence interval [CI], 0.45–0.92) and one-dose vaccination (OR, 0.60; 95% CI, 0.43–0.83). Two-dose vaccination compared to no vaccination was associated with a lower risk of persistent fatigue (OR, 0.62; 95% CI, 0.41–0.93) and pulmonary disorder (OR, 0.50; 95% CI, 0.47–0.52). Among those with ongoing long COVID symptoms, 54.4% (95% CI, 34.3–73.1%) did not report symptomatic changes following vaccination, while 20.3% (95% CI, 8.1–42.4%) experienced symptomatic improvement after two weeks to six months of COVID-19 vaccination. Conclusions: COVID-19 vaccination before SARS-CoV-2 infection was associated with a lower risk of long COVID, while most of those with ongoing long COVID did not experience symptomatic changes following vaccination.